Relasi Etis Pendidik dan Peserta Didik dalam Kitab Ayyuhal Walad: Relevansi Pemikiran Al-Ghazali bagi Pendidikan Karakter di Indonesia - Siti Zainab Yusran; Hairul Hudaya (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2026)
This study analyzes the ethical relationship between educators and learners in Ayyuhal Walad by Imam Al-Ghazali and examines its relevance to character education in Indonesia. Contemporary educational practice tends to prioritize cognitive outcomes while neglecting ethical and relational dimensions in learning. A qualitative library research design was employed, applying thematic content analysis through the six-phase procedure of Braun and Clarke (2022). All twelve principal exhortations (mawa'izh) of Ayyuhal Walad served as the analytical corpus, yielding 27 initial codes consolidated into three core themes. The findings reveal that Al-Ghazali's ethical educator–learner relationship rests on three integrated pillars: exemplarity (qudwah), requiring educators to embody the knowledge they transmit; sincere intention (niyyah), orienting learning toward moral rather than instrumental ends; and ethical conduct (adab) governing relational behavior in pedagogical interactions. These pillars mutually presuppose one another, forming a transformative pedagogical relationship directed at learners' moral development. The study demonstrates that Al-Ghazali's framework aligns with contemporary findings on teacher–student relationships, value-based motivation, and character education. This study contributes by systematically operationalizing Al-Ghazali's classical thought, showing that his ethical framework is not merely normative but concretely applicable to contemporary character education in Indonesia.